Rab27A Is Present in Mouse Pancreatic Acinar Cells and Is Required for Digestive Enzyme Secretion - Hou, Yanan (PLoS One, 2015)
The small G-protein Rab27A has been shown to regulate the intracellular trafficking of secretory granules in various cell types. However, the presence, subcellular localization and functional impact of Rab27A on digestive enzyme secretion by mouse pancreatic acinar cells are poorly understood. Ashen mice, which lack the expression of Rab27A due to a spontaneous mutation, were used to investigate the function of Rab27A in pancreatic acinar cells. Isolated pancreatic acini were prepared from wild-type or ashen mouse pancreas by collagenase digestion, and CCK- or carbachol-induced amylase secretion was measured. Secretion occurring through the major-regulated secretory pathway, which is characterized by zymogen granules secretion, was visualized by Dextran-Texas Red labeling of exocytotic granules. The minor-regulated secretory pathway, which operates through the endosomal/lysosomal pathway, was characterized by luminal cell surface labeling of lysosomal associated membrane protein 1 (LAMP1). Compared to wild-type, expression of Rab27B was slightly increased in ashen mouse acini, while Rab3D and digestive enzymes (amylase, lipase, chymotrypsin and elastase) were not affected. Localization of Rab27B, Rab3D and amylase by immunofluorescence was similar in both wild-type and ashen acinar cells. The GTP-bound states of Rab27B and Rab3D in wild-type and ashen mouse acini also remained similar in amount. In contrast, acini from ashen mice showed decreased amylase release induced by CCK- or carbachol. Rab27A deficiency reduced the apical cell surface labeling of LAMP1, but did not affect that of Dextran-Texas Red incorporation into the fusion pockets at luminal surface. These results show that Rab27A is present in mouse pancreatic acinar cells and mainly regulates secretion through the minor-regulated pathway.